Karamata theorem for regularly log-periodic functions - Buldygin, V. V.; Pavlenkov, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We generalize the Karamata theorem on the asymptotic behavior of integrals with variable limits to the class of regularly log-periodic functions.